STRATEGI NATION BRANDING KOLOMBIA MELALUI KAMPANYE “LA RESPUESTA ES COLOMBIA” - Iqbal Valensyah Purwanto; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The following study describes Colombia's nation branding practice that was implemented during Juan Manuel Santos' administration in 2010-2018. Colombia itself is a country located in South America that is often associated with a rather negative image and perception due to three critical issues that happened within the country: drug trafficking, insecurity and corruption. In order to create a positive image of its country, Colombia later implemented its own nation branding strategy through the